On defining a prophet : atheological-ethical study of the Balaam narratives of Numbers 22-24 - Ward, Herbert D., Jr. (Stellenbosch : Stellenbosch University, 2009)
Thesis (DTh (Old and New Testament))--Stellenbosch University, 2009.